Comparação biomecânica entre os exercícios de pilates com alta e baixa intensidade em pacientes com dor lombar crônica - Oliveira, Victor Bruno Soares de (2024)
Introduction: Chronic low back pain (CLBP) is a prevalent musculoskeletal condition globally, ranking as the third most disabling in Brazil. CLBP poses clinical challenges and significant healthcare costs associated with psychosocial factors. While pharmacological treatment faces controversies, physical exercise, particularly the Pilates method, emerges as an effective recommendation. This study aimed to compare muscle activity and movement quality in high and low-intensity Pilates exercises in patients with CLBP, aiming to fill gaps in understanding biomechanical compensations and optimize therapeutic strategies for the condition. Methods: 52 individuals were selected based on eligibility criteria to investigate the influence of Pilates method intensity on movement biomechanics in CLBP patients. The sample included participants with persistent CLBP for more than 12 weeks, aged 18 to 60 years, and sedentary. Participants were divided into two distinct groups: Group 1, subjected to low-intensity Pilates method (n=26), and Group 2, subjected to high-intensity Pilates method (n=26). Results: There were no significant differences in sociodemographic data between groups. Significant differences were observed in electromyography only in the latissimus dorsi muscle during the Reformer exercise, with higher muscle activation in the high-intensity group (MD= 4.7, 95% CI 0.7–8.6). Among all kinematic variables, only trunk flexion differed between groups in the three analyzed exercises. The high- intensity group showed greater trunk flexion in Reformer (MD= 6.9°, 95% CI 2.9–10.9°) and Chair exercises (MD= 4.9°, 95% CI 1.0–8.9°), and less trunk flexion in the Cadillac exercise (MD= -6.6, 95% CI -8.9 – -4.2). Conclusion: The intensity of exercise can influence the biomechanical alteration of trunk flexion movement, as well as demonstrate greater activation of the latissimus dorsi muscle in individuals with CLBP.